TEXNOLOGIYALÍQ TÁLIM SABAQLARÍNDA ZAMANAGÓY PEDAGOGIKALÍQ TEXNOLOGIYALARDAN PAYDALANÍW METODIKASÍ - Djumagulov, Zinatdin Uzakbergenovich; Seytniyazova, Gawhar Baxtiyar qızı (SCIENCE and SOCIETY, 2026)
This article provides an in-depth scientific analysis of the methodology for using modern pedagogical technologies in technology education lessons. In particular, interactive methods, project-based learning, problem-based learning, STEAM integration, and the didactic potential of information and communication technologies are examined. The research employed theoretical analysis, experimental methods, observation, and statistical data processing. The findings demonstrate that modern pedagogical technologies significantly enhance students’ theoretical knowledge, practical skills, creative thinking, and independent learning competencies.